Design and development of installer tool for file handle - Mohd Amran, Norshila; Razali, Nizamuddin; Soon Chong, Johnson Lim; Othman, Hasyamuddin; Rohanai, Reyanhealme (Penerbit UTHM, 2021)
This study discussed the tool installer's development process for File Handle to facilitate handle mounted on a file. This study aims to help the lab assistant who has trouble making the installation process for file handle where the files should have the installation neat and undamaged. Therefore, in this study, the Tools Installer File Handle study was developed to solve their problems in making the files' installation process handle more effectively. This is a product development study based on the ADDIE model with five phases: Analysis, Design, Development, Implementation, and Evaluation. The study involved laboratory assistants in the Faculty of Technical and Vocational Education (FPTV) University Tun Hussein Onn Malaysia (UTHM) in the mechanical field as experts in the final phase. The experts evaluated the functionality of the product. The expert evaluation and validation findings for Installer Tool File Handle show a high percentage of the suitability of the design and installation functions as a tool. In conclusion, this study proves that the product "Installer File Handle" is suitable for laboratory assistants to handle files' installation process and make the process more effective and reduce working time.